2020
DOI: 10.1080/10872981.2020.1742965
|View full text |Cite
|
Sign up to set email alerts
|

Project-based learning approach to increase medical student empathy

Abstract: This study investigated the impact of empathy training on medical students using a project-based learning approach on the development of their empathic abilities. Study participants were Year 2 students in the six-year medical program, to whom a one credit-hour course on empathic communication was offered over a semester. In this course, students worked on collaborative team projects in which they were asked to interview a person and to report the empathy that they shared with the interviewee. Development in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
1
26
0
4
Order By: Relevance
“…First, various educational interventions targeted toward increasing dental students’ empathy can be effective in enhancing the patient-centered attitude of medical and dental students. Previous studies suggested students’ reflection on how effective their interviews with simulated patients were in terms of empathic communication, and project-based learning approach helps students in developing their empathy [ 43 , 49 ]. Second, this study suggests that students with low empathic concern and high personal distress may need intensive support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, various educational interventions targeted toward increasing dental students’ empathy can be effective in enhancing the patient-centered attitude of medical and dental students. Previous studies suggested students’ reflection on how effective their interviews with simulated patients were in terms of empathic communication, and project-based learning approach helps students in developing their empathy [ 43 , 49 ]. Second, this study suggests that students with low empathic concern and high personal distress may need intensive support.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Korean version of the IRI (K-IRI) that was translated and validated by Kang et al [ 42 ] was used. This K-IRI has been used to assess empathy among Korean medical students and is found to have adequate psychometric properties [ 43 ]. The IRI was designed to measure individual differences in empathy among the general population.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the present ndings suggest that students with low empathic concern and fantasy and high personal distress type of empathy may be at a higher risk of employing physician-centered practicing style and may need more intensive training support. Several studies have shown the effectiveness of various educational interventions in developing medical student empathy [42,60]. Therefore, curricula targeted to increase empathic concern and fantasy type of empathy and decrease personal distress type of empathy can be effective in enhancing the patient-centered attitudes of medical and dental students.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Korean version of the IRI (K-IRI) that was translated and validated by Kang et al [41] was used. This K-IRI has been used to assess empathy for Korean medical students and is found to have adequate psychometric properties [42]. The IRI was designed to measure individual differences in empathy among the general public.…”
Section: Interpersonal Reactivity Index (Iri)mentioning
confidence: 99%
“…We were intrigued by Kim's paper [1]. As senior medical students in the UK, it is our opinion that Medical Schools serve to enhance and maintain intrinsic empathy, as opposed to teaching an individual how to be empathetic [2].…”
Section: Dear Editormentioning
confidence: 99%